EU’s human rights dialogues with Belarus and the developments around presidential elections - Madalin-Catalin Blidaru, (Technium Social Sciences Journal, 2020)
. The 2020 presidential elections in Belarus were characterised by widely recognised human rights violations. The European Union decided not to recognise the results after important declarations and consultations among its leaders. However, the European Union and Belarus were engaged in a structured human rights dialogue. The author discusses the links between the human rights dialogue as a foreign policy instrument and the dynamics around the 2020 presidential elections in Belarus. The hypothesis stresses that the evolution of the bilateral dialogues provides information on the developments within the relations between the European Union and Belarus. The case study, based on extensive analysis of official documents, finds additional support for the claim against the effectiveness of the human right s dialogues with third parties. Apart from a better understanding and a channel of dialogue with the country, the human rights topics recreated an environment in which it justified the return to restrictions and sanctions against individuals involved in illegitimate actions. The historical analysis of the presidential elections, particularly the climate around their organisation, the assessment of the human rights dialogues as a policy tool, and the analysis of the official dialogues on the thematic areas of concerns from the human rights dialogues support this hypothesis.